Congetture alle Metamorfosi di Apuleio - Lucarini, Carlo M. (Hyperboreus, 2022)
The aim of this paper is to cast new light on the textual constitution of some passages of Apuleius´ Metamorphoses. Ca. 40 pieces are discussed and for the most part of them a new solution is proposed; in the other cases I argue for a solution already proposed, bur not accepted by the editors.